Impact of agronomy on HT-2 and T-2 toxin content of oats. - Edwards, Simon G.; Anderson, Eric (Plant Breeding and Seed Science, 2011)
Surveys of oats in the UK and Nordic countries have identified high concentrations of HT-2 and T-2 can occur in unprocessed oats. HT-2 and T-2 are two closely related type A trichothecenes and two of the most toxic fusarium mycotoxins. There is currently no legislation on HT-2 and T-2, however, there is a discussion limit of 500 µg kg-1 in unprocessed oats. A previous survey identified that variety, previous crop, cultivation, fungicide use and some other factor(s) within organic oat production, which was not within the model, were all significant agronomic factors in the determination of HT-2 and T-2 concentrations of UK oats. Possible agronomy within conventional compared to organic agriculture would include the use of inorganic fertilisers and plant growth regulators (PGR). Oats harvested from two series of agronomic field experiments were analysed for the combined concentration of HT-2 and T-2 (HT2+T2) using ELISA. Experiments were repeated for both winter and spring varieties over two years. The first experiments were of a factorial design with three varieties, three nitrogen rates and plus/minus a PGR (chlormequat). The second series had twelve fungicide regimes. The results identified that there were no significant differences in HT-2+T-2 between samples from oat plots that received different rates of inorganic nitrogen, a PGR, or a range of different fungicide regimes. There was however a significant difference between varieties for both winter and spring variety experiments...